2020
DOI: 10.3390/ma13194233
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Mechanical Characterization of Dry Three-Dimensional Warp Interlock Para-Aramid Woven Fabrics: Experimental Methods toward Applications in Composite Reinforcement and Soft Body Armor

Abstract: Recently, three-dimensional (3D) warp interlock fabric has been involved in composite reinforcement and soft ballistic material due to its great moldability, improved impact energy-absorbing capacity, and good intra-ply resistance to delamination behaviors. However, understanding the effects of different parameters of the fabric on its mechanical behavior is necessary before the final application. The fabric architecture and its internal yarn composition are among the common influencing parameters. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…In Figure 14, by the help of scanning electron microscopy, one may see the fibrillation, thinning and rupture of the aramid fibrils, resulting from the process of destroying a thread on the 2nd layer. The values for BFS (back face signature) for the LFT SB1 plus package are given in Table 1 and are measured according to Ballistic Resistance of Body Armor, NIJ Standard-0101.06 [2] (see also Figure 3).…”
Section: Results and Discussion Of Failure Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 14, by the help of scanning electron microscopy, one may see the fibrillation, thinning and rupture of the aramid fibrils, resulting from the process of destroying a thread on the 2nd layer. The values for BFS (back face signature) for the LFT SB1 plus package are given in Table 1 and are measured according to Ballistic Resistance of Body Armor, NIJ Standard-0101.06 [2] (see also Figure 3).…”
Section: Results and Discussion Of Failure Mechanismsmentioning
confidence: 99%
“…A recent tendency of research in trying to improve the response of aramid fabrics to ballistic impact is the 3D architecture [2], but fabrics with unidirectional layers with different angle orientation in sublayers is also intensively used for body armor, due to the fact that the strength of the yarns is not "consumed" in bending them in a 2D or 3D architecture. Of course, technology is obliged to find the adequate film and yarns for maintain these multi-axial orientations in a single layer.…”
Section: Materials and Testing Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the different interlinking depth of the warp yarn through the weft layers, the average thickness of each fabric’s variants was found to be different (1.42, 1.44, 1.52, and 1.63 mm for variants 8/0, 8/4, 8/8, and 4/8, respectively). The parameter, design and manufacturing processes of the fabrics were also discussed in detail in our previous research work [ 59 ]. Four armour panel systems having surface areas of 50 × 50 cm 2 and comprising nonbonded but angled 8-panels (40 layers) from each 3D warp interlock variant were prepared ( Figure 2 a).…”
Section: Materials and Testing Methodsmentioning
confidence: 99%
“…The articles included in the Special Issue explore the development of sustainable composites with valorized manufacturability for a breakthrough from conventional practices and corresponding to the Industrial Revolution 4.0 ideology. The publications revealed that the application of nano-particles improves the mechanical performance of composite materials [ 6 ]; advanced woven fabrics efficiently reinforce soft body-armor [ 7 ]; heat-resistant aluminum composites ensure the safety of overhead power transmission lines [ 8 ]; chemical additives can help in detecting temperature impact on concrete structures [ 9 ]. The publications [ 10 , 11 ] investigated connection problems of high-performance composites.…”
mentioning
confidence: 99%